Key performance indicators for biogas production—methodological insights on the life-cycle analysis of biogas production from source-separated food waste. (1st June 2020) - Feiz, Roozbeh; Johansson, Maria; Lindkvist, Emma; Moestedt, Jan; Påledal, Sören Nilsson; Svensson, Niclas
Abstract: The anaerobic digestion of food waste can not only enhance the treatment of organic wastes, but also contributes to renewable energy production and the recirculation of nutrients. These multiple benefits are among the main reasons for the expansion of biogas production from food waste in many countries. We present methodological insights and recommendations on assessing the environmental and economic performance of these systems from a life-cycle perspective. We provide a taxonomy of the value chain of biogas from food waste which describes major activities, flows, and parameters across the value chain with a relatively high detail. By considering the multiple functions of biogas production from food waste, we propose a few key performance indicators (KPI) to allow comparison of different biogas production systems from the perspectives of climate impact, primary energy use, nutrients recycling, and cost. We demonstrate the operational use of our method through an example, where alternatives regarding the heat supply of the biogas plant are investigated. We demonstrate how global and local sensitivity analyses can be combined with the suggested taxonomy and KPIs for uncertainty management and additional analyses. The KPIs provide useful input into decision-making processes regarding the future development of biogas solutions from food waste. Highlights: Multi-level and life-cycle-based taxonomy of biogas production from food waste. Methodological recommendations to improve and complement life-cycle analysis. Integrating three different functions of biogas production. Seven key performance indicators to capture multiple functions of biogas production. A hypothetical example demonstrating the use of the suggested method.